Speciation and Pre-Concentration of Selenium with Nano-ZnO as Absorbent in Environmental Samples - Ting Huang (Adsorption Science & Technology)
In this study, zinc oxide nanoparticles (nano-ZnO) were used as adsorbent for the separation and pre-concentration of selenium(IV) from aqueous solution. The selenium(IV) was determined by hydride generation-atomic fluorescence spectrometry with KBH 4 –HCl. The adsorption percentage of selenium(IV) was 93% at pH 4.0–8.0, and the elution percentage of Se(IV) exceeds 96% with 0.5 ml of 0.5 mol l −1 NaOH. The adsorption equilibrium data best fitted with the Langmuir isotherm model and the maximum adsorption capacity was 31.45, 31.75 and 31.95 mg g −1 at 273, 333 and 353 K, respectively. The detection limit of selenium(IV) (3σ, n = 11) was 1.60 µg l −1 and the relative standard deviation was 4.24%. This process has been successfully applied for the determination of trace selenium(IV) in some environmental samples and satisfactory results were obtained.